Trade Developments in 2016 : Policy Uncertainty Weighs on World Trade - Constantinescu, Cristina (World Bank, Washington, DC, 2017)
This edition of Global Trade Watch addresses three questions concerning recent trade developments: What is happening? Why? Does it matter? 2016 is the fifth consecutive year of sluggish trade growth and the year with the weakest trade performance since the aftermath of the 2008 global financial crisis. Current estimates of growth in the volumes of trade in goods and services range from 1.9 percent to 2.5 percent; preliminary high-frequency data suggest that merchandise trade volumes may have grown by slightly above 1 percent. The year 2016 is different from the other post crisis years, in that trade sluggishness is a characteristic of both advanced and emerging economies.